English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

1/sinN is equal to cscN and cotN is equal to cosN/sinN so
1/sinN - cosN/1 x cosN/ sinN
1/sinN - cosN(squared)/ sinN
1 - cosN(squared)/sinN
sinN(squared) +CosN(squared) = 1 so
sinN(squared)/ sinN
sinN

2006-12-14 08:22:30 · answer #1 · answered by sam 1 · 0 0

1/sinN is equal to cscN and cotN is equal to cosN/sinN so
1/sinN - cosN/1 x cosN/ sinN
1/sinN - cosN(squared)/ sinN
1 - cosN(squared)/sinN
sinN(squared) +CosN(squared) = 1 so
sinN(squared)/ sinN
sinN

2006-12-15 00:15:09 · answer #2 · answered by arpita 5 · 0 0

OK here we go...
First: we know that Csc N=1/Sin N
and Cos N X Cot N =Cos^2 N /Sin N

So by production we'll have: (1/ Sin N) - ( Cos^2 N / Sin N)
By common dinaminator : ( 1- Cos^2 N) / Sin N
We know that: 1 - Cos^2 N = Sin^2 N
So we have now: Sin^2 N / Sin N
By simplifying we have: (Sin N) and thats the answer.

2006-12-14 16:27:35 · answer #3 · answered by alireza_ofu 2 · 0 0

cscN - cosN x cotN
=>1/sinN - cosN X cosN/sinN.........writing in simplified form
=>[1-(cosN)^2]/sinN............taking LCM
=>(sinN)^2/sinN.............since (sinN)^2 + (cosN)^2=1
=>sinN

2006-12-17 09:52:50 · answer #4 · answered by sushant 3 · 0 0

fedest.com, questions and answers